Study on the regeneration process and overall performance of a microencapsulated phase change material slurry dehumidification system - Niu, Xiaofeng; Ke, Qing; Wang, Zhaohua; Zhou, Junming; Dong, Honglin; Mahian, Omid (Renewable energy)
Building on previous findings that showed the efficacy of microencapsulated phase change materials (MicroPCM) in augmenting liquid desiccant dehumidification performance, this study endeavors to further explore the extent of the impact of MicroPCM in the regeneration and the entire dehumidification system. The results of the regeneration experiment on the microencapsulated phase change material slurry (MPCMS) reveal that the addition of MicroPCM impedes regeneration. Specifically, as the concentration of MicroPCM increases, both the regeneration rate and the MPCMS concentration after regeneration decrease, while the regeneration effectiveness exhibits an initial decline followed by an increase. An empirical correlation was proposed to predict the regeneration rate of MPCMS for their future application. The results showed that the addition of MicroPCM led to a decrease in the regeneration rate by as much as 48.1%, when compared to a pure LiCl solution. However, a simulation analysis of the entire system revealed that within a certain concentration range of MicroPCM addition, the coefficient of performance (COP) of the system could still be increased by up to 4.28%. This finding suggests that if a more suitable non-heating regeneration method were used, the addition of MicroPCM could further enhance the overall performance of the liquid desiccant dehumidification system.